A Sensitivity Analysis of Cross-Country Growth Regressions - Levine, Ross; Renelt, David (American Economic Review, 1992)
A vast literature uses cross-country regressions to search for empirical linkages between long-run growth rates and a variety of economic policy, political, and institutional indicators. This paper examines whether the conclusions from existing studies are robust or fragile to small changes in the conditioning information set. We find that almost all results are fragile. We do, however, identify a positive, robust correlation between growth and the share of investment in GDP and between the investment share and the ratio of international trade to GDP. We clarify the conditions under which there is evidence of per capita output convergence.